Последние свидетели: сто недетских колыбельных / Светлана Алексиевич - Алексиевич Светлана Александровна (Пальмира, 2004)
Экземпляры: ЦБ (20221027) / Инвентарный номер: 38102 / Цена: 91.50 / Сис.шифр: Р2 / Авт.знак: А 48 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6